DETERMINANTS OF CARBON EMISSION DISCLOSURE: THE ROLE OF INDUSTRY SENSITIVITY, MEDIA EXPOSURE, AND ENVIRONMENTAL PERFORMANCE - Sistya Rachmawati; Etty Murwaningsari; Yuha Nadhirah Qintharah; Qintharah, Yuha Nadhirah (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2025)
The purpose of this study is to determine and analyze the Effect of Industry Sensitivity, Media exposure, Environmental Performance and Profitability on Carbon Emission Disclosure. The research method used in this study is quantitative. The data for this study uses secondary data from companies listed on the Indonesia Stock Exchange (IDX). The companies used are groups of consumer non-cyclical & Energy sector companies listed on the Indonesia Stock Exchange in 2022-2024. The sampling method in this study is purposive sampling. The data collected were 126 companies after statistical data analysis using eviews-12 software. Based on the test results, the industry sensitivity variable has a negative effect on carbon emission disclosure, the media exposure variable has a negative effect on carbon emission disclosure, the environmental performance variable has a positive effect on carbon emission disclosure, and the profitability variable has a negative effect on carbon emission disclosureKeywords: Industry Sensitivity, Media exposure, Environmental Performance, Profitability, Carbon Emission Disclosure